A DIFFERENCE IN INTRADIALYTIC BLOOD PRESSURE IN CHRONIC RENAL FAILURE PATIENTS WITH INTERDIALYTIC WEIGHT GAINS> 5% AND - Ni Made Srianti (NURSING UPDATE : Jurnal Ilmiah Ilmu Keperawatan P-ISSN : 2085-5931 e-ISSN : 2623-2871, 2021)
Background: Hemodialysis, which is one of the therapies performed on patients with kidney failure when the kidneys are unable to function or have malfunctioned. Although hemodialysis is classified as safe and beneficial for patients, it does not mean that it does not have side effects, namely IDWG> 5% and <5% which make changes in intradialytic blood pressure. Objective: This study aimed at determining the differences between intradialytic blood pressure in chronic kidney failure patients with IDWG> 5%. and <5% in the hemodialysis room at RSD Mangusada Badung. Method: The study had been done with a comparative analytic design with a cross-sectional approach. The total samples were 58 people with the incidental sampling technique. Data were collected using a digital weight scale and a mercury sphygmomanometer. Data were analyzed using the Mann-Whitney test. Results: The results of the study with IDWG> 5% with the mean systolic intradialytic blood pressure of 101.79 mmHg and diastolic mean 75.43 mmHg and IDWG <5% with the mean systolic blood pressure of 115.73 mmHg and a diastolic mean of 83.42 mmHg. Analysis of differences in intradialytic blood pressure in patients with chronic renal failure with IDWG> 5% and <5% obtained a p-value of 0.001. Conclusion: There was a difference in intradialytic blood pressure in chronic renal failure patients with IDWG> 5% and <5% in the hemodialysis room at RSD Mangusada Badung. The recommendations of this study are expected to be input for nurses to always provide education about dietary patterns related to IDWG to minimize intradialytic complications